Financial Literacy and Investment Performance of Household Investors in Jaffna District - Pirathajiny, M.; Anandasayanan, S. (Sri Lanka Finance Association., 2023)
This study is designed to evaluate the impact of financial literacy on the investment performance of household investors in Jaffna district. Financial literacy is the independent variable, and investment decision is the dependent variable. Independent variable is measured using numeracy, interest compounding, inflation, time value of money, and money illusion. Financial literacy is essential in today's advanced and complex financial nature. The reason is that high financial literacy is linked to a country's high economic development. If the country's citizens, whose productive population is currently dominated by investors, are financial literate, then its economic development can improve because the people can manage their money, especially for savings and investments. A questionnaire was developed to collect the primary data for this study. Survey data have been collected from 480 household investors using the convenience sampling method because of crisis time. The reliability analysis of the questionnaire shows an acceptable range. Regression and correlation analysis have been done to analyze the data. Investor's performance is significantly correlated with numeracy, interest compounding, inflation, time value of money, and money illusion. Findings show that financial literacy significantly impacts household investors' investment performance. Further, this study contributes to existing knowledge in this area, regulators and policymakers to consider these findings to take concern about the financial literacy of individual household investors.
Keywords: Financial Literacy; Household investors; Investment performance